Are taxes good for your health? - Paddy Carter; Alex Cobham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The global framework for financing development, adopted in 2015, places great emphasis on mobilizing domestic resources to finance the Sustainable Development Goals, which include universal healthcare. In a recent paper Reeves et al. (2015) attribute progress towards universal healthcare to higher levels of taxation, but report a negative association between taxes on goods and services (indirect taxes) and health outcomes, which they hypothesise arises from the impact such taxes have on the real incomes of the poor. This paper revisits the relationship between tax types and health outcomes using the ICTD Government Revenue Dataset, which, crucially, isolates taxes from resource industries. As expected, we confirm increases in revenue are associated with increased public health expenditure; we find some weak evidence that greater reliance on direct taxes is associated with higher health spending and better outcomes, but no evidence that indirect taxes are deleterious to health. We argue these relationships cannot bear the weight of causal interpretation but that they offer some guidance on what to expect from increased domestic revenue mobilization.
Keywords: I1; H2; H51; H42; 330; taxation; health; resource revenues